Wykorzystanie modelu ekonometrycznego w prognozowaniu cen surowców w przemyśle tekstylnym - Welc, Jacek (Using econometric model in forecasting prices of raw materials in textile industry, 2005)
The paper presents the possibility of building six-months-ahead forecasts of price of imported flax fibre used in production process of Orzel Linen Mills. To that end the simple econometric model has been constructed. The model includes lagged prices of domestic flax fibre, lagged values of two textile price indeces in United States and two seasonal dummy variables. The model enables prediction of imported flax fibre price with high degree of accuracy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 275-284